2020
DOI: 10.26466/opus.644988
|View full text |Cite
|
Sign up to set email alerts
|

Grup Sanat Terapisi Programının Ergenlerin Mutluluk Düzeyleri, Duyguları İfade Etme Eğilimi ve Duygu Düzenleme Güçlüğüne Etkisi

Abstract: Bu çalışmanın amacı araştırmacılar tarafından geliştirilen Yapılandırılmış Grup Sanat Terapisi Programının, 15-18 yaş aralığındaki ergenlerin mutluluk düzeyleri, duygularını ifade etme eğilimleri ve duygu düzenleme güçlüklerine etkisini incelemektir. Araştırmacılar tarafından, Gross'un süreç modelinden alınan öncül odaklı stratejiler ve tepki odaklı stratejiler temel alınarak, sanat terapisi teknikleriyle 11 oturumluk bir program hazırlanmıştır. Program ile ulaşılmak istenen amaçlar 'duyguların farkındalığı', … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…As a result, it can be said that the findings obtained from the first hypothesis of the study are similar to the results of previous studies examining the possible effects of programs developed for emotion regulation on individuals (Karataş, 2020;Gem, 2018;Urcan, 2018;Aktürk, 2016;Ulusoy, 2016;Gülgez & Gündüz, 2015;Davıd & Dobrean, 2014;Schwarz et al, 2013;Horn et al, 2011;Izard et al, 2008;Stark et al, 2008;Clyne & Blampied, 2004).…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 87%
See 1 more Smart Citation
“…As a result, it can be said that the findings obtained from the first hypothesis of the study are similar to the results of previous studies examining the possible effects of programs developed for emotion regulation on individuals (Karataş, 2020;Gem, 2018;Urcan, 2018;Aktürk, 2016;Ulusoy, 2016;Gülgez & Gündüz, 2015;Davıd & Dobrean, 2014;Schwarz et al, 2013;Horn et al, 2011;Izard et al, 2008;Stark et al, 2008;Clyne & Blampied, 2004).…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 87%
“…It is concluded that the Structured Group Art Therapy Program developed by Karataş (2020) is effective in increasing adolescents' happiness levels and their tendency to express their emotions and decrease their emotion difficulties and psychiatric symptoms. In the research conducted by Gülgez & Gündüz (2015), it is seen that the Dialectical Behavior Therapy Based Emotion Regulation Program is effective in reducing the emotion regulation difficulties of university students.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…Existing empirical evidence shows that art therapy is an effective psycho-social intervention method in emotion regulation processes. When the studies in the literature are examined, the positive effects of art therapy practices on individuals' emotion regulation processes are seen (Gruber & Oepen, 2017;Kang et al, 2014;Karataş & Güler, 2020;Sitzer & Stockwell, 2015). The findings obtained from our research are consistent with the results of these studies.…”
Section: Discussionsupporting
confidence: 86%
“…In one of the few group studies focused on art activities to increase self-efficacy, the effects of a structured group counseling program focused on art therapy on the happiness levels, tendency to express emotions, and difficulties in regulating emotions of adolescents aged 15-18 were examined. The results of the study revealed that the impulse subscale decreased in the emotion regulation difficulties of the individuals in the experimental group, the positive emotion subscale increased in the happiness variable, and the positive and closeness dimension increased in the tendency to express emotions (Karataş and Güler 2020). In another study, the effect of structured art therapy group work applied to clients with bipolar disorder on self-esteem was examined.…”
Section: Discussionmentioning
confidence: 97%
“…The related literature studied the effects of art therapy on various psychiatric and physical patient groups and adolescents. For example, in some studies, the effects of art therapy on symptom profile, insight, and social functioning, positive and negative symptoms and alexithymia level, and personal and social skills in patients with schizophrenia (Sarandöl et al 2013, Günay 2017, Ataseven 2018, the effect on the quality of life of children with cancer (Özcan 2012), the effect of art therapy method applied to older people with dementia on cognitive status (Bulduk et al 2017) and the effect on body perception, happiness levels, the tendency to express emotions, difficulty in regulating emotions, and psychiatric symptoms in adolescents (Tunç 2007, Karataş 2016) have been searched. Since the number of studies based on artistic activities for adolescents is limited, this study aims to conduct a study based on artistic practices in adolescents.…”
Section: Introductionmentioning
confidence: 99%